2023
DOI: 10.2147/prbm.s420711
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Learning Burnout on Mobile Phone Dependence Among Adolescents in Western China Under the “Double Reduction” Policy: The Mediating Role of Social Support

Rong Wu,
Yuan Luo,
Pengyu Ren
et al.

Abstract: Purpose This paper investigated the prevalence of mobile phone dependence (MPD) and its associated with learning burnout under the “double reduction” policy among adolescents in Guizhou Province in western China. In addition, the influence of the mediating mechanism of social support on this relationship was investigated. Methods The sample was collected from 16,216 adolescents in West China’s Guizhou province, from December 2021 to January 2022 via multistage stratifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 80 publications
1
4
0
Order By: Relevance
“…Specifically, it was found that mobile phone dependence partially and positively predicts academic burnout, mediated by academic engagement. These findings support hypotheses 1 and 2, aligning with previous research (30,45). The results suggest a negative correlation between the level of mobile phone dependence and the level of commitment to learning, as well as a positive correlation between mobile phone dependence and academic burnout.…”
Section: The Mediating Role Of Learning Engagementsupporting
confidence: 90%
“…Specifically, it was found that mobile phone dependence partially and positively predicts academic burnout, mediated by academic engagement. These findings support hypotheses 1 and 2, aligning with previous research (30,45). The results suggest a negative correlation between the level of mobile phone dependence and the level of commitment to learning, as well as a positive correlation between mobile phone dependence and academic burnout.…”
Section: The Mediating Role Of Learning Engagementsupporting
confidence: 90%
“…The research group " Health Status Survey of Middle School Students in Guizhou Province, China" provided the sample population for this study, which consisted of middle school students registered in the province (excluding junior high, high school, and vocational secondary school students who were not enrolled in school for various reasons, declined to be investigated, or experienced other mental health issues during the investigation period) [52]. In this sample population, combined with the de nition of returned migrant middle school students in this study [6,7], subjects: middle school students (junior middle school students, high school students, and vocational middle students) who have had the experience of living or studying (≥ 6 months) with both parents (including step-parents, adoptive parents) or one parent leaving their place of residence (" place of migration ") to the place where they work (" place of migration ").…”
Section: Participantsmentioning
confidence: 99%
“…During the investigation, 18838 questionnaires were distributed; 1233 students returned incomplete surveys, yielding a 93.45% recovery rate. 16,216 student questionnaires were ultimately included for examination in the rst two data analyses, yielding an effective recovery rate of 92.11% [52]. Based on this sample size, 2,020 returned migrant middle school students were chosen as the research subjects based on the previously mentioned exclusion screening.…”
Section: Study Datamentioning
confidence: 99%
“…The subjects of this study collected from the sample population of the research group Health Status Survey of middle School Students in Guizhou province, China, which was the middle school students in Guizhou province (excluding junior high school, high school, and vocational middle school students who were not in school during the survey period, refused the survey and suffered from other psychiatric disorders due to various reasons; (Wu et al, 2023). In this sample population combined with the de nition of returned migrant middle school students in this study (Duan et al, 2017;Han, 2020), middle school students who met the following conditions were selected as the study subjects: those who had followed both parents (including stepparents and adoptive parents) or one parent out of their household registration (referred to as the out ow area) to lived or studied (≥ 6 months) in the non-household registration area where they worked (referred to the in ow area).…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Each city (state) was selected from each stratum (a total of 3 cities states, i.e., Zunyi city, Qiannan prefecture, and Qiandongnan prefecture), 6 junior high schools, 4 senior high schools, and 2 vocational middle schools were randomly selected from each city (state; a total of 36 middle schools), and in each stratum after strati cation by grade 4 classes were randomly selected, and a total of 14 classes in each school were selected (a total of 432 classes), a total of 18,838 questionnaires were distributed, and the information was deleted. 1,233 incomplete questionnaires and 16,216 valid questionnaires were recovered, with a recovery rate of 93.45% (Wu et al, 2023). Based on this sample data, 2,020 returned migrant middle school students were nally obtained as the study population based on the above nerf screening, including 1,020 male students (50.5%), 1,000 female students (51.1%), 751 junior high school students (37.2%), 870 senior high school students (45.7%), and 346 middle school students (17.1%) in Fig.…”
Section: Study Datamentioning
confidence: 99%